2018
DOI: 10.1177/0300060518778477
|View full text |Cite
|
Sign up to set email alerts
|

Application of cystourethroscopy during tracheobronchial foreign body removal in children

Abstract: ObjectiveThis study aimed to describe preliminary experiences associated with removal of tracheobronchial foreign bodies (TFBs) by cystourethroscopy (CU).MethodsWe performed a retrospective analysis of 127 paediatric cases of TFB removal by CU at our centre from January 2009 to August 2016. Data that were extracted from the medical records included age, sex, location and nature of the TFBs, operation time, and complications.ResultsAll TFBs were successfully removed by CU. The mean time of the procedure was 3.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Out of the 14,471 cases in this review article, only 2551 reported a positive history of FBA and its associated complications. The rate of this event was 100% in Denmark 46 and Italy, 47 whereas India 17,18 (57.9%) and China 6,7,20–26,34,36,37 (52.8%) had the lowest witness rates. As presented in Table 4, Asian patients reported a higher number of choking history, while Europeans had fewer witnesses of FBA.…”
Section: Results and Descriptions Of The Included Studiesmentioning
confidence: 93%
See 4 more Smart Citations
“…Out of the 14,471 cases in this review article, only 2551 reported a positive history of FBA and its associated complications. The rate of this event was 100% in Denmark 46 and Italy, 47 whereas India 17,18 (57.9%) and China 6,7,20–26,34,36,37 (52.8%) had the lowest witness rates. As presented in Table 4, Asian patients reported a higher number of choking history, while Europeans had fewer witnesses of FBA.…”
Section: Results and Descriptions Of The Included Studiesmentioning
confidence: 93%
“…After screening and reviewing the articles, 14,471 cases were evaluated with 2852 females (40%) and 4290 males (60%) being the majority. India, 17,18 Pakistan, 19 and China 7,20–26 had the highest male‐to‐female ratios, while Sweden 14 and Iran 8 had ratios closer to 1. We were unable to determine the precise number of pediatric males and females from 12 articles 6,27–37 .…”
Section: Results and Descriptions Of The Included Studiesmentioning
confidence: 98%
See 3 more Smart Citations